2020
DOI: 10.1186/s13018-020-02063-0
|View full text |Cite
|
Sign up to set email alerts
|

Does patellofemoral osteoarthritis affect functional outcomes and survivorship after medial unicompartmental knee arthroplasty? A meta-analysis

Abstract: Purpose The argument that patellofemoral osteoarthritis (PFOA) is a contraindication to unicompartmental knee arthroplasty (UKA) remains to be resolved. The purpose of this study was to perform a meta-analysis to determine whether PFOA affects functional outcomes and survivorship after medial UKA. Methods A literature search was performed in PubMed, Medline, Cochrane Library and Web of science to identify studies published in English (the last search was updated on June 1, 2020). The primary outcome measure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The impact of such coexistence has been explored in multiple research projects. Lu et al [ 124 ], Deckard et al [ 125 ], and Ercan et al [ 126 ] concluded that whether coexisting OA is present does not significantly affect the outcome. Burger et al [ 127 ] concluded that mild to moderate preoperative radiological degenerative changes, and mal-alignment of the PF joint are not associated with unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of such coexistence has been explored in multiple research projects. Lu et al [ 124 ], Deckard et al [ 125 ], and Ercan et al [ 126 ] concluded that whether coexisting OA is present does not significantly affect the outcome. Burger et al [ 127 ] concluded that mild to moderate preoperative radiological degenerative changes, and mal-alignment of the PF joint are not associated with unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This study found no statistically significant relationship between intraoperative of patellofemoral joint findings and severity of JSW L , and therefore agrees with other papers that conclude that the state of the patellofemoral joint should not be considered a contraindication in UKA. 31 - 33 …”
Section: Discussionmentioning
confidence: 99%
“…This study found no statistically significant relationship between intraoperative of patellofemoral joint findings and severity of JSW L , and therefore agrees with other papers that conclude that the state of the patellofemoral joint should not be considered a contraindication in UKA. [31][32][33] The main limitation of the study was that some of the unrevised UKAs implanted 15 years ago or more did not have radiographs at 15 years. Therefore, the sample may not be representative of the whole cohort and may underestimate the incidence of lateral OA.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, there had been debates on whether patellofemoral joint degeneration affects the outcome of unicompartmental knee replacement. 13,14 In our study, we attempted to minimize the influence of patellofemoral joint degeneration when comparing the outcomes between UKR and TKR groups. Hence, we matched the two groups of patients both radiologically and functionally.…”
Section: Discussionmentioning
confidence: 99%